2004
DOI: 10.1530/rep.1.00025
|View full text |Cite
|
Sign up to set email alerts
|

Environmental anti-androgens and male reproductive health: focus on phthalates and testicular dysgenesis syndrome

Abstract: The amount of research into endocrine disruption has exploded over the past decade and a re-evaluation of the state of research in this area is timely. There are debates about whether human male reproductive health is really declining and whether endocrine disrupting chemicals play any role in the perceived decline. Most data currently conclude that there are wide geographical variations in semen quality and in the incidence of testicular cancer, cryptorchidism and hypospadias. This review aims to give a brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
214
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(228 citation statements)
references
References 66 publications
3
214
0
7
Order By: Relevance
“…23 It has been hypothesized that endocrine disrupting compounds play a major role in the aetiology of increased incidence of testicular dysgenesis syndrome which gathers decreased quality of semen, cryptorchidism, hypospadias and testicular cancer. 24 Chemicals with hormone-like activity can also disrupt programming of endocrine signalling pathways during development. Indeed, androgen and oestrogen receptors, which play critical but distinct roles in the physiology of sperm cells, are present on male germ cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 It has been hypothesized that endocrine disrupting compounds play a major role in the aetiology of increased incidence of testicular dysgenesis syndrome which gathers decreased quality of semen, cryptorchidism, hypospadias and testicular cancer. 24 Chemicals with hormone-like activity can also disrupt programming of endocrine signalling pathways during development. Indeed, androgen and oestrogen receptors, which play critical but distinct roles in the physiology of sperm cells, are present on male germ cells.…”
Section: Introductionmentioning
confidence: 99%
“…23 It has been hypothesized that endocrine disrupting compounds play a major role in the aetiology of increased incidence of testicular dysgenesis syndrome which gathers decreased quality of semen, cryptorchidism, hypospadias and testicular cancer. 24 Chemicals with hormone-like activity can also …”
mentioning
confidence: 99%
“…Vinclozolin is a fungicide used in agricultural fruit crops, such as grapes for the wine industry (Kelce et al 1994, Fisher 2004. Vinclozolin is an anti-androgenic compound that is metabolized into further anti-androgenic compounds (Kelce et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the fetal hormonal disruption induced either by chemical anti-androgens such as flutamide or by different environmental anti-androgen compounds (e.g., vinclozolin, phthalates) gives rise to a wide range of reproductive system abnormalities such as hypospadias, undescended testes, developmental testicular alterations (Fisher 2004, Crews & McLachlan 2006, Gray et al 2006, Newbold et al 2006, and particularly to a long-term apoptosis of germ cells in the adult testis (Omezzine et al 2003, Bozec et al 2004, Uzumcu et al 2004 transmitted by male through at least four generations (Anway et al 2005). These observations support the concept of a fetal and transgenerational programming of adult testicular germ cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%